Impact Analysis of Student's Role in the Teaching Campus Program - Mayasari, Novi; Indriani, Ari; Ika R, Okta (KnE Social Sciences, 2022)
The Teaching Campus Program (KM) is one program of the Directorate of Learning and Student Affairs and the Directorate General of Higher Education. It is one form of implementing the goals of the Independent Learning Independent Campus (MKBM). In the KM, students are responsible for assisting in learning activities, technology adaptation, and administration at the school to which they are assigned. This program has been developed since learning had not been fully effective during the pandemic. This study aimed to determine the impact of the student’s role in teaching at SD Negeri Bakalan 1 Kapas Bojonegoro. The data collection techniques used were observation, interview and documentation. Then, the collected data were processed using qualitative data processing techniques by Miles and Hubermen. The results of the study indicated that the implementation of the Teaching Campus Program batch III 2022 at SD Negeri Bakalan 1 Kapas Bojonegoro included three aspects; the first in teaching, students did this in both face-to-face learning and online learning. Second, in adaptation technology, the students assisted teachers in making teaching media and materials in accordance with the curriculum. Third, in administration, the students helped teachers in the preparation of learning tools. Keywords: Teaching Campus; MBKM; elementary students.